Privacy in practice: professional discourse about information control in health care. Issue 2 (11th April 2016) - Anthony, Denise L.; Stablein, Timothy
Abstract : Purpose: – The purpose of this paper is to explore different health care professionals' discourse about privacy – its definition and importance in health care, and its role in their day-to-day work. Professionals' discourse about privacy reveals how new technologies and laws challenge existing practices of information control within and between professional groups in health care, with implications not only for patient privacy, but also for the role of information control in professions more generally. Design/methodology/approach: – The authors conducted in-depth, semi-structured interviews with n =83 doctors, nurses, and health information professionals in two academic medical centers and one veteran's administration hospital/clinic in the Northeastern USA. Interview responses were qualitatively coded for themes and patterns across groups were identified. Findings: – The health care providers and the authors studied actively sought to uphold the protection (and control) of patient information through professional ethics and practices, as well as through the use of technologies and compliance with legal regulations. They used discourses of professionalism, as well as of law and technology, to sometimes accept and sometimes resist changes to practice required in the changing technological and legal context of health care. The authors found differences across professional groups; for some, protection of patient information is part of core professional ethics, while for others it is simply part of their occupational work, aligned with organizational interests. Research limitations/implications: – This qualitative study of physicians, nurses, and health information professionals revealed some differences in views and practices for protecting patient information in the changing technological and legal context of health care that suggest some professional groups (doctors) may be more likely to resist such changes and others (health information professionals) will actively adopt them. Practical implications: – New technologies and regulations are changing how information is used in health care delivery, challenging professional practices for the control of patient information that may change the value or meaning of medical records for different professional groups. Originality/value: – Qualitative findings suggest that professional groups in health care vary in the extent of information control they have, as well in how they view such control. Some groups may be more likely to (be able to) resist changes in the professional control of information that stem from new technologies or regulatory policies. Some professionals recognize that new IT systems and regulations challenge existing social control of information in health care, with the potential to undermine (or possibly bolster) professional self-control for some but not necessarily all occupational groups.